The New Effective Model of Financing Without Providing Collateral and Free of Risk for Developing Small and Medium Enterprises - Ridwan, Agus; Poespowidjojo, Donny Abdul Latief (Serials Publications Pvt. Ltd, 2017)
The practice of financing management is a critical component of the organization’s safety climate. Mudharabah financing is known to be suitable for small business financing, but requires collateral as one of the financing conditions to the sharia bank which is always a barrier for Small and Medium Enterprises in obtaining financing. The alternative model built to be used in financing this small business combines Mudharabah and Musyarakah concepts, and is called The Rotating Multiple Wheels Management Model. This model involves small and medium-sized businesses, but does not require collateral for avoiding all risks of Mudharabah Financing, namely: (i) Side Stream Risk, (ii) Neglect Risk, (iii) Manipulation Risk. This model can be used by banks in assisting the development of financing to Small and Medium Enterprises by minimizing risk to the minimum level, while also facilitating Small and Medium Enterprises in obtaining bank financing without collateral. However, this study does not examine the morale of parties involved in the financing process to small and medium-sized businesses so that the failure of financing due to moral hazard is not included in this model.